PENGARUH PEMBERIAN BOOKLET JATUH TERLUKA (JATUR) PADA GURU SD TERHADAP PENINGKATAN PENGETAHUAN PERTOLONGAN PERTAMA PADA ANAK DI SD UMP - Salsa, Salsa Nurinta; Fatwati Fitriana, Nurul (Universitas Kadiri, 2023)
Students are at high risk of emergencies as various incidents can occur within this group. Additionally, children spend significant time at school, increasing their risk of injury. Emergencies can happen unexpectedly and anywhere, including at home, on the road, and within the school environment. Most injuries in children are directly related to physical activities outside, with many injuries occurring during school hours. This study was quasi-experimental, focusing on one group without randomization. The design employed a pre-and post-test approach using the Wilcoxon test. The study was conducted in May 2023 with 38 respondents. Results: Based on the results, the